In the footsteps of research in the Faculty of Nursing at U de A - Salazar Maya, Ángela (Investigación y Educación en Enfermería, 2012)
This year, on the 24th of August, we commemorated 25 years since the creation of the Research Center at the Faculty of Nursing (CIFE, for the term in Spanish). Celebrating this date implies visiting the past and rescuing the events that permitted its creation and development. The Center, a project by Dean Liria Pérez (1983 - 1985), had as main objectives to continue promoting research among professors and editing a scientific journal.1 It was approved by the Superior Council on 24 August 1987,2 when Cecilia Soto was Dean. The CIFE began operating under the direction of Professor Marta Lucía Toro (1987-1989). In 1989, the CIFE Technical Committee (TC) evaluated the state of research in the Faculty and considered it a priority for its advancement the creation of groups to develop lines of research. One of the most important results by the Center, along these years, was when it held the Forum on Nursing Practices1 in 1990, which concluded with the proposal to stimulate the development of research to contribute in the elaboration of protocols for care, validation of nursing models, and which could help in the construction of standards to improve the quality of care at different levels.